The Level of Applying the "NCATE" Standards in the Faculty of Education, University of Khartoum from the Point of View of Faculty Members - Saifaldin Idris Onia; Adil Mohammed Dafallah; Fadlalmawla Abdulradi Alshaikh (University of Science and Technology, Yemen, 2020)
This study aimed to identify the level of applying the "NCATE" Standards in the Faculty of Education, University of Khartoum, from the faculty members' perspective. To achieve this objective, the descriptive method was used by administering a questionnaire on a sample of 51 faculty members. The questionnaire consisted of 54 items divided into 6 fields: Offered Programs, System of Assessment and Evaluation, Diversity, Field Experience, Professional Development of Staff, Resources and Governance. The data were analyzed by using one sample T-test, and Mann-Whitney test for the difference between the independent grade averages, and the analysis of variance. The results showed a moderate level of the "NCATE" Standards in the Faculty of Education, from the faculty members' perspective. There were no differences between males and females in applying the "NCATE" Standards in the Faculty of Education except in the system of assessment and evaluation in favor of males. Also, there were no differences in the "NCATE" Standards from the faculty members' perspective attributed to the academic rank. The study recommended conducting more studies about the obstacles of applying the "NCATE" Standards in the Faculty of Education, University of Khartoum. Keywords: NCATE, Faculty of Education, University of Khartoum, the staff.